Experimental warming interacts with soil moisture to discriminate plant responses in an ombrotrophic peatland. (26th May 2015) - Buttler, Alexandre; Robroek, Bjorn J.M.; Laggoun‐Défarge, Fatima; Jassey, Vincent E.J.; Pochelon, Cédric; Bernard, Gregory; Delarue, Frédéric; Gogo, Sébastien; Mariotte, Pierre; Mitchell, Edward A.D.; Bragazza, Luca; Morgan, John
Abstract Question A better understanding of the response of Sphagnum mosses and associated vascular plants to climate warming is relevant for predicting the carbon balance of peatlands in a warmer world. Open‐top chambers (OTCs) have been used to investigate the effect on soil biogeochemical processes in peatlands, but little information is available on the effects of OTCs on microclimate conditions and the associated response of the plant community. We aimed to understand how simulated warming and differences in soil moisture affect plant species cover. Location A Sphagnum‐dominated peatlands in French Jura. Methods We used OTCs to measure the effect of a near‐ground temperature increase (+1.5 °C on average) on vegetation dynamics over five growing seasons (2008–2012) in a Sphagnum‐dominated peatland, in two adjacent microhabitats with different hydrological conditions – wet and dry. Microclimatic conditions and plant species abundance were monitored at peak biomass in years 1, 2, 3 and 5 and monthly during the plant growing season in year 5. Results The response to warming differed between vascular plants and bryophytes, as well as among species within these groups, and also varied in relation to soil moisture. Andromeda polifolia abundance responded positively to warming, while Vaccinium oxycoccus responded negatively, and Eriophorum vaginatum showed a high resistance. Conclusion Depth of rooting of vascular plants appeared to control the response in plant abundance, while moss abundance depended on various other interacting factors, such as shading by the vascular plant community, precipitation and soil moisture.